2022
DOI: 10.1007/s00125-022-05712-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk of type 2 diabetes modifies the effects of a lifestyle intervention aimed at the prevention of gestational and postpartum diabetes

Abstract: Aims/hypothesis The aim of this study was to assess the interaction between genetic risk and lifestyle intervention on the occurrence of gestational diabetes mellitus (GDM) and postpartum diabetes. Methods The RADIEL study is an RCT aimed at prevention of GDM and postpartum diabetes through lifestyle intervention. Participants with a BMI ≥30 kg/m2 and/or prior GDM were allocated to intervention and control groups before pregnancy or in early pregnancy. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
2
8
1
Order By: Relevance
“…Contrary to our results, many studies,29–32 including our own during pregnancy and first postpartum year,19 have shown an association between a type 2 diabetes PRS and glycemic outcomes. Similar to our study, many studies have also addressed women with a history of GDM 30–32.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to our results, many studies,29–32 including our own during pregnancy and first postpartum year,19 have shown an association between a type 2 diabetes PRS and glycemic outcomes. Similar to our study, many studies have also addressed women with a history of GDM 30–32.…”
Section: Discussioncontrasting
confidence: 99%
“…After adjusting for age, HLS was associated with reduced risk of glycemic abnormalities only among women at highest genetic risk of type 2 diabetes. This is well in line with our previous findings from pregnancy and the first postpartum year 19. In the total study sample, however, the HLS associated with health benefits such as a lower BMI and body fat percentage, highlighting the importance of supporting healthy lifestyle among all postpartum women.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results indicated that even the milder degrees of gestational hyperglycemia diagnosed by the more stringent IADPSG criteria still had a higher risk of subsequent progression to T2DM and pre-diabetes. Genetic predisposition might be one possible contributor to the progression to T2DM after GDM as increasing evidence have indicated that GDM may share similar genetic susceptibilities with T2DM ( 23 26 ). Genome wide association studies (GWAS) and other studies have reported that several genetic variants (such as MTNR1B, TCF7L2, IGF2BP2, CDKAL1, GCK ) are associated with increased risk of both GDM and T2DM, suggesting that these conditions might have a shared genetic background ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%